LA CARACTERIZACIÓN MUSICAL TRANSMEDIA DE LAS IDENTIDADES JUVENILES: EL CASO DE LA SERIE STRANGER THINGS - Dr. Antonio Francisco ALAMINOS-FERNÁNDEZ (Fonseca, Journal of Communication, 2023)
Audio-visual productions, such as television series, use youth stereotypes that reflect reality and simultaneously construct it by disseminating simplified models that are used as codes for social labelling. Social types are characterized by a set of personal traits, social environment, clothing, lifestyle, etc. In the characterization of the characters, the use of musical re-sources has been studied to a lesser extent